2008
DOI: 10.1158/0008-5472.can-07-6011
|View full text |Cite|
|
Sign up to set email alerts
|

Diphenyl Difluoroketone: A Curcumin Derivative with Potent In vivo Anticancer Activity

Abstract: Diphenyl difluoroketone (EF24), a molecule having structural similarity to curcumin, was reported to inhibit proliferation of a variety of cancer cells in vitro. However, the efficacy and in vivo mechanism of action of EF24 in gastrointestinal cancer cells have not been investigated. Here, we assessed the in vivo therapeutic effects of EF24 on colon cancer cells. Using hexosaminidase assay, we determined that EF24 inhibits proliferation of HCT-116 and HT-29 colon and AGS gastric adenocarcinoma cells but not of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
173
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 41 publications
6
173
0
1
Order By: Relevance
“…Studies to date have indicated that poor absorption and rapid metabolism of curcumin severely curtail its bioavailability. Because of this limitation on the therapeutic use of curcumin, structural modifications of this agent has been attempted to increase its absorption and bioavailability (20)(21)(22). However, it is too early to predict their experimental and clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have indicated that poor absorption and rapid metabolism of curcumin severely curtail its bioavailability. Because of this limitation on the therapeutic use of curcumin, structural modifications of this agent has been attempted to increase its absorption and bioavailability (20)(21)(22). However, it is too early to predict their experimental and clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…It has asurprisingly wide range of beneficial properties, including anti-inflammatory, antioxidant, chemopreventive and chemo-therapeutic activity and has been used to treat several different cancers [3][4][5]. However, although curcumin is non-toxic and has promising anti-cancer activities, preclinical and clinical studies indicate that its poor bioavailability and weak pharmacokinetic profiles derived from its structural instability under physiological conditions have seriously limited its application in anti-cancer therapies [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, although curcumin is non-toxic and has promising anti-cancer activities, preclinical and clinical studies indicate that its poor bioavailability and weak pharmacokinetic profiles derived from its structural instability under physiological conditions have seriously limited its application in anti-cancer therapies [6,7]. In the past two decades, alot of efforts has been put into the chemical modification of curcumin to identify potential analogues with better bioavailability and antitumor activities [5,[8][9][10]. The title compound, one of monocarbonyl curcumin analogues has demonstrated excellent cytotoxic properties against several human cancer cell lines in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…EF24, with ortho-fluorinated phenyl group exhibited anticancer activity in vitro when tested using breast cancer, colon cancer and ovarian epithelial cancer. [19][20][21] Its para-fluorinated derivative H-4073 was more potent than EF24 in inducing cytotoxicity to ovarian cancer cells. [21][22][23] DAP compounds have also been shown to be more readily bioavailable than the parent compound, curcumin.…”
Section: Introductionmentioning
confidence: 99%